Efficient routes to racemic and enantiomerically pure (S)-BINOL diesters - Costantino, Andrea Rosana (2013)
A systematic study for esterification procedures to the synthesis of BINOL diesters is described. Reaction conditions with TFAA and 85% H3PO4 were selected as the best procedure to prepare enantiomerically pure (S)-BINOL diesters VIII to XI with almost quantitative yields and very low reaction times.